Performance of a direct-injection natural gas engine with multiple injection strategies. (15th December 2019) - Li, Menghan; Liu, Gengfei; Liu, Xiaori; Li, Zhijie; Zhang, Qiang; Shen, Boxiong
Abstract: This paper presents the experimental results for the performance of a direct-injection natural gas marine engine with different multiple injection strategies. In order to investigate the effects of natural gas post injection proportion and natural gas injection separation, a series of tests were performed at five different injection proportions (8%, 10%, 15%, 20%, 25%) and injection separation from 100μs to 700 μs at every 100 μs. The averaged cylinder pressure traces and combustion parameters (MFB50%, MFB90% and MFB5-90%) of each test point were calculated for combustion analysis. HC, CO and NOx emissions were collected to reveal the emissions characteristics. The results showed that the peak values of cylinder pressure and heat release rate will be lower than that of natural gas single injection strategy when multiple natural gas injection strategies are applied. Though the phase angle of 50% mass fraction burned is advanced at medium natural gas injection separations, the phase angle of 90% mass fraction burned is more likely to occur early at longer natural gas injection separations. With regard to emissions, HC and NOx emissions can benefit from using shorter natural gas injection separations while CO can only be reduced with small post injection proportions with certain natural gas injection separations. Highlights: Multiple injection strategies are applied on a direct-injection natural gas engine. Using multiple injection strategies results in lower maximum pressure. HC and NOx emissions can be improved by using shorter injection separations. CO emissions are reduced at small post injection proportions and selected separations.